A clinical study of evaluation of different modalities of treatment and etiologies of stricture urethra - Raykar, Raviraj R.; Jadhav, Ravikumar R. (International Surgery Journal, 2019)
Background: Urethral strictures are a common urological problem presenting in day to day urological practice. There has been change in the etiology of urethral strictures with traumatic one’s accounting for majority of them in recent times. Newer treatment modalities like VIU and various kinds of urethroplasty have revolutionized its management and significantly contributed towards improvement of quality of life among these patients. The objective for this study were to study the various aetiologies and different modalities of treatment for urethral strictures. Methods: A 23 cases of urethral strictures aged 5-75 years admitted in the surgical wards of KIMS, Hubballi were included in the present study. Mean age of presentation was 34.5 years. Detailed history and physical examination were recorded. Relevant investigations like ASU and MCU were performed and recorded. These patients were treated by various surgical procedures considered appropriate as per the patient individual needs. Results: Mean age was 34.5 years in the present study. Most of the patients presented with obstructive voiding symptoms, straining (65.1%) and poor stream (56.4%). Majority of strictures were of traumatic etiology (60.8%) followed by inflammatory (34.7%) and iatrogenic strictures (4.3%) in the present study. Bulbar urethra was the most commonly involved site (65.1%) followed by posterior urethra (30.4%), penile urethra (17.4%) and meatal stricture (4.3%). Most of the patients presenting with retention of urine were managed by SPC. Both VIU and urethroplasty had good success rates of 72.7% and 80% respectively. Conclusions: Most of the strictures were of traumatic etiology. VIU and urethroplasty were found to be effective means of treating urethral strictures.